(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In this work, we investigated the performance of parabolic trough solar collector with hot water generation system for 3 days day time. We observed the differences in temperature in the range of 6.7Â°C to 24Â°C.Â The average beam radiation during the testing period is 658W/m2. The temperature difference, useful heat gain, wind velocity, direct beam radiation, absorber temperature and solar flux are found in the test period from 9.00 a.m to 16.00 p.m. Â